Towards a framework for continuous and discrete multidimensional systems - Rabenstein, Rudolf; Trautmann, Lutz (Zielona Góra: Uniwersytet Zielonogórski)
Continuous multidimensional systems described by partial differential equations can be represented by discrete systems in a number of ways. However, the relations between the various forms of continuous, semi-continuous, and discrete multidimensional systems do not fit into an established framework like in the case of one-dimensional systems.
Keywords: multidimensional systems; partial differential equations; transfer functions; wave digital models